2015
DOI: 10.1101/gr.197517.115
|View full text |Cite
|
Sign up to set email alerts
|

Worldwide patterns of genomic variation and admixture in gray wolves

Abstract: The gray wolf (Canis lupus) is a widely distributed top predator and ancestor of the domestic dog. To address questions about wolf relationships to each other and dogs, we assembled and analyzed a data set of 34 canine genomes. The divergence between New and Old World wolves is the earliest branching event and is followed by the divergence of Old World wolves and dogs, confirming that the dog was domesticated in the Old World. However, no single wolf population is more closely related to dogs, supporting the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

33
265
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 184 publications
(315 citation statements)
references
References 65 publications
33
265
2
Order By: Relevance
“…Unlike the SNP-based analysis described above, single-sample genotype calling was performed with no particular ascertainment scheme, and we restricted our analysis to eight canid genomes with coverage ranging from 8 to 24 × . When we included only modern dogs, we observed that wolf populations appeared to diverge rapidly, concordant with previous studies2627, whereas the branching of the main dog lineages took place over a much longer period of time. We found that the (uncalibrated) dog–wolf divergence time in units of expected numbers of mutations per site (0.5247 × 10 −4 ) was similar to that reported in Freedman et al 26…”
Section: Resultssupporting
confidence: 89%
“…Unlike the SNP-based analysis described above, single-sample genotype calling was performed with no particular ascertainment scheme, and we restricted our analysis to eight canid genomes with coverage ranging from 8 to 24 × . When we included only modern dogs, we observed that wolf populations appeared to diverge rapidly, concordant with previous studies2627, whereas the branching of the main dog lineages took place over a much longer period of time. We found that the (uncalibrated) dog–wolf divergence time in units of expected numbers of mutations per site (0.5247 × 10 −4 ) was similar to that reported in Freedman et al 26…”
Section: Resultssupporting
confidence: 89%
“…In contrast, haplotypes in clade A have more limited distributions centered in southern-central European countries. This pattern, together with archaeological, morphological and genetic findings, suggest that extant Old and New World wolf populations expanded during or right after the last glacial period, balancing the local extinction of ancient wolf ecomorphs [53,56,6568]. However, it is not known if the turnover of wolf populations has been the consequence of a generalized megafaunal extinction wave due to climate changes or to hunting pressure and/or competition with expanding modern human populations [69–71].…”
Section: Discussionmentioning
confidence: 99%
“…(Wayne 1986;1993;Vilà et al, 1997;Fan et al, 2016). Thirty years research, with unbelievable progress in methods, and broadening of the database have confirmed this statement in many ways.…”
Section: Dogs Are Wolvesmentioning
confidence: 90%
“…Now we accept that western Eurasians carry a significant percentage of Neandertal genes, and in the Far East, Denisovan genes indicate the importance of regional adaptations (e.g., Pagani et al, 2016). Our dogs' ancestry is no longer that ideal pedigree, fit to be endorsed by the American Kennel Club, but more like a brushwood, lines of decent changing with every new study (e.g., Vilà et al, 1997;Freedman et al 2014;Frantz et al 2016;Fan et al 2016). The exchange of genes between dogs and wolves continues till today, and wolves are split into numerous clades, with specific traits (e.g., tundra wolves vs. forest wolves.…”
Section: Humans and Fauna In The Southern Fringes Of The Mammoth Steppementioning
confidence: 99%